Investigation of infill-patterns on mechanical response of 3D printed poly-lactic-acid. (July 2020) - Aloyaydi, Bandar; Sivasankaran, Subbarayan; Mustafa, Ammar
Abstract: This paper presents the effect of infill patterns (IPs) on the mechanical response of 3D printed specimens by conducting the low-velocity impact test (LVI) and compression test. The poly-lactic acid (PLA, purity 98 wt% >) material has selected and printed using fused deposition modeling (FDM, speed 20 mm/s, layer height 0.2 mm, no of layers 30, extruded at 200 °C) with four different IPs: triangle, grid, quarter cubic, and tri-hexagon. The LVI test on velocity-time, energy-time and force-displacement, and the compression responses have examined and presented in this study. The LVI test was carried out to determine the penetration energy level, energy absorption capacity (toughness), stiffness, and strength of PLA porous parts (60% infill density) for implant/tissue/recyclable product applications. The results have shown that the triangular pattern has produced the highest absorbed energy in LVI test (penetration energy 7.5 J, and stiffness 668.82 N/mm) due to more sheared/contact layers' perpendicular to impactor (hemispherical insert); while the grid pattern exhibited the highest compressive strength (72 MPa) due to more layers aligned along the compressive loading direction The SEM fracture surface image of Triangular IP has produced effective raster and layer bonding, less number of voids, more amount of circular beach markings, and absence of ratchet lines leading to possess improved mechanical properties. Highlights: Four infill patterns of triangle, grid, quarter cubic, and tri-hexagon were printed by FDM. Triangular IP exhibited highest penetration limit velocity (0.28 m/s). Triangular IP produced maximum stiffness (669 N/mm). Grid IP displayed more compressive strength (72 MPa). SEM surface topography and fractography were examined.